THE INFLUENCE OF COMPENSATION, MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEES JOB SATISFACTION AT PT NIKKO CAHAYA ELECTRIC - Waspodo, Agung AWS; Dharmawan, Rio; Handaru, Agung Wahyu (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this study were: 1) To know the description of compensation, motivation, career development and job satisfaction of employees at PTNikko Cahaya Electric, 2) To determine whether there is influence between compensation on job satisfaction of employees at PT Nikko Cahaya Electric, 3) To determine whether there is influence between motivation on employee job satisfaction at PT Nikko Cahaya Electric, 4) To determine whether there is influence between career development on employee job satisfaction at PT Nikko Cahaya Electric, 5) To determine whether there is influence between compensation, motivation and career development together on job satisfaction of employees at PTNikko Cahaya Electric, and 6) To know how much contribution of compensation, motivation and career development on employee job satisfaction at PT Nikko Cahaya Electric. The sample of this research are 60 employees of PTNikko Cahaya Electric. Research data retrieval by survey method with questionnaires and the data processed with SPSS version 20. This research using descriptive and explanatory analysis. The results of regression showed that there is positive and significant correlation between compensation on job satisfaction,there is positive and significant correlation between motivation on job satisfaction, there is positive and significant correlation between career development on job satisfaction. Compensation, motivation and career development simultaneously have positive and significant impact on job satisfaction. Keywords: Compensation, Motivation, Career Development, Job Satisfaction